Reaktualisasi Pembelajaran Menulis Naskah Drama pada Generasi Z dengan Metode Discovery Learning Berbasis Artificial Intelligence (CHAT GPT) - Fauziyah, Lutfiatul; Haryanto, Muhammad (Edu Berkah Khatulistiwa, 2024)
Learning to write a playwright at school is often presented in a theoretical form and is considered a difficult, unpleasant, time-consuming, and difficult task in developing ideas. Based on this phenomenon, the author proposes a concept by combining discovery learning and artificial intelligence (GPT) methods in the learning of drama writing. This conceptual idea aims to support the development of digital education in Indonesia in line with the Merdeka Curriculum. This research uses qualitative methods with a conceptual approach. From the results of this study, learning to invent the script of the Z generation with the method of discovery learning based on artificial intelligence (Chat GPT) shows that there are six stages of the phenomenon: (a) giving incentives, (b) identifying problems, (c) collecting data, (d) managing information, (e) proofing, (f) drawing conclusions. Research results show that the application of AI-based discovery learning methods can enhance student interactiveness in the learning process, support online collaboration, and facilitate real-time feedback, which is relevant in contemporary education. However, this study needs to be further developed into applied research to test its empirical value of effectiveness in improving the Z-generation script writing skills in the era of independent curricula.